Trace Metal Element Analysis in Some Seafood in the Coastal Zone of the Red River (Ba Lat Estuary, Vietnam) by Green Sample Preparation and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) - Nhu Da Le; Thi Thu Ha Hoang; Vu Phong Phung; Thi Lien Nguyen; Thi Thuy Duong; Le Minh Dinh; Thi Mai Huong Pham; Thi Xuan Binh Phung; Tien Dat Nguyen; Thanh Nghi Duong; Thi My Hanh Le; Phuong Thu Le; et al. (Journal of Analytical Methods in Chemistry)
Fisheries and aquaculture production in the coastal zone of Vietnam contribute significantly to the national economy. However, seafood quality and safety, especially in terms of metal contents, are of increasing concern, for both domestic and international markets. This paper presents the results of an investigation in some trace metal elements (iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), arsenic (As), cadmium (Cd), and mercury (Hg)) concentrations in some fishes, crustaceans, and molluscs in the coastal zone of the Red River (in the Ba Lat estuary in Thai Binh and Nam Dinh provinces) during four sampling campaigns in 2020. All samples were treated by a green sample preparation using microwave digestion and then analyzed by inductively coupled plasma-mass spectrometry (ICP-MS). The results showed that the trace metal element concentrations in fish, crustacean, and mollusc samples decreased in the following order: Fe > Zn > Mn > Cu > As > Cd ∼ Hg. In more details, the ranges of trace metal elements in seafood samples were 13.13–202.73; 7.63–82.71; 0.48–22.73; 0.72–15.58; 0.18–5.12; 0.001–1.114; and 0.001–0.923 mg·kg−1 for Fe, Zn, Mn, Cu, As, Cd, and Hg, respectively. The research results contribute to the dataset of the seafood (both fishery and aquacultural seafood) quality in the Red River coastal zone. Although the mean values of different trace metal elements observed in this study were lower than the allowed values of Vietnam’s or European’s threshold for food safety, some high concentrations were detected. The survey results suggest the need to expand the monitoring scope (frequency of monitoring, number of samples, and observed variables) for obtaining a fully comprehensive assessment of seafood quality in this region. Our results also indicate that it is necessary to manage water quality in coastal areas, especially where aquaculture activities are carried out.